PENGARUH MEDIA MAKET PLAYDOUGH TERHADAP KECERDASAN VERBAL LINGUISTIK ANAK USIA 5-6 TAHUN: Aa Mursaluna, Susi Herlinda, Nopa Wilyanita - Mursaluna, Aa; Herlinda, Susi; Wilyanita, Nopa (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2024)
The purpose of this study was to determine whether playdough mock-up media influences verbal linguistic intelligence for children aged 5-6 years in TK Negeri Pembina 2 Pekanbaru. The research method that the researchers used is Quasi experiment and Nonequivalent Control Group Design. There are two classes used, namely the control class and the experimental class, where each class is carried out in 2 stages namely, the pretest stage (before being treated) and the posttest stage (after treated). The research sample of 30 children, 15 children each. From the test results using SPSS Windows ForVer 17, obtained sig 0.185 statistics is much greater than 0.05 (0.185> 0.05), thus it can be concluded that the research data is homogeneous. Based on the "Paired Sampels test" output table, the sig value is known. (2-tailed) is 0.001 <0.005, then H0 is rejected and Ha is accepted. So it can be concluded that there are differences in verbal linguistic intelligence of children aged 5-6 years between before and after the use of playdough mockup media in the experimental class. Based on the calculation results showed an increase in verbal linguistic intelligence in the Experiment group included in the moderate category because the gain value obtained was 0.65 at 0.3> g?0.7. This means that there is an influence of playdough mock media on verbal linguistic intelligence for children aged 5-6 years in TK Negeri Pembina 2 Pekanbaru.